Postharvest handling : a systems approach - Brueckner, Bernhard; Florkowski, Wojciech J.; Prussia, Stanley E.; Shewfelt, Robert L. (Food science and technology international series, 2014)
Revised and update, this second edition explores the logistics of handling fruits and vegetables from a varietyof perspectives. Leading experts present important insights into postharvest handling under varying weather conditions, assuring quality control, changes in consumer habits and other key factors including overall supply chain management